PEMBANGUNAN BUDAYA ANTIKORUPSI KETERKAITANNYA DENGAN PENGATURAN HUKUM TENTANG PERAN SERTA MASYARAKAT DALAM PEMBERANTASAN KORUPSI DI INDONESIA - Kumbul Kusdwidjanto Sudjadi; Diah Ratu Sari Harahap (Ensiklopedia of Journal, 2022)
The crime of corruption an extraordinary crime, because the impact is extraordinary, so extraordinary efforts are needed to overcome it, one of which is the participation of the community. Community participation in eradicating corruption has basically been regulated in Article 41 paragraph (1) of Law Number 31 of 1999 concerning the eradication of criminal acts of corruption which states that the community can participate in assisting efforts to prevent and eradicate corruption. The research location is the Corruption Eradication Commission, with the legal research methodology used is normative-empirical. The conclusion of this study states that to make community participation effective, it is necessary to have a firm and binding rule as a legal umbrella for the community regarding what things can be played, awards received and of course also required sanctions for individuals who do not play a role. and, especially dare to report if in the surrounding environment there are allegations of corruption. The existence of these sanctions is expected to spur or force the public to be responsible and dare to fight corruption, because those who do not carry out will be subject to sanctions for them. This is done because the crime of corruption is an extraordinary crime, as is the case with narcotics crimes, in which there is also an element of coercion for the public to want to participate in the eradication of narcotics crimes. The development of an anti-corruption culture is very much needed in Indonesia, because the crime of corruption, which is considered an extraordinary crime in terminology, is already considered normal because it has become a habit or culture in society.Keywords: Anti-corruption, Program, Village, KPK.